2022
DOI: 10.3390/plants12010081
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced-Efficiency Fertilizers Impact on Nitrogen Use Efficiency and Nitrous Oxide Emissions from an Open-Field Vegetable System in North China

Abstract: Open vegetable fields in China are a major anthropogenic source of nitrous oxide (N2O) emissions due to excessive nitrogen (N) fertilization. A 4 yr lettuce experiment was conducted to determine the impacts of controlled-release fertilizers (CRFs) and nitrification inhibitors (NIs) on lettuce yield, N2O emissions and net economic benefits. Five treatments included (i) no N fertilizer (CK), (ii) conventional urea at 255 kg N ha–1 based on farmers’ practice (FP), (iii) conventional urea at 204 kg N ha–1 (OPT), (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…In comparison with conventional urea, DCRU significantly decreased the GWP. The decrease in GWP under CRU and DCRU was mainly due to the reduced N 2 O emissions, which was in accordance with previous studies [ 16 , 18 , 27 ]. Therefore, the reasonable application of DCRU may be an important measure for slowing down GHG emissions from vegetable systems in the future.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In comparison with conventional urea, DCRU significantly decreased the GWP. The decrease in GWP under CRU and DCRU was mainly due to the reduced N 2 O emissions, which was in accordance with previous studies [ 16 , 18 , 27 ]. Therefore, the reasonable application of DCRU may be an important measure for slowing down GHG emissions from vegetable systems in the future.…”
Section: Discussionsupporting
confidence: 92%
“…CRU can better match fertilizer nutrient release with crop uptake without additional topdressing [ 10 , 12 , 13 ]. Previous meta-analyses indicated that CRU could be applied once as basal fertilizer with no effect on grain yields while reducing reactive N losses by 49% worldwide [ 14 ], thus decreasing the use of N fertilizer and promoting time- and labor-saving crop production [ 15 , 16 ]. The advantageous effects of CRU on grain yield and NUE depend largely on the synchronization of the N release rate with the N requirements of crops [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Significant research efforts have thus been dedicated to stabilizing urea in the environment via the design of various chemically stabilized urea condensation polymers, such as ureaforms, that confine urea into a polymeric structure, urease enzyme inhibitors that delay urea hydrolysis, nitrification inhibitors that reduce the activity of nitrifying bacteria, and polymer-or sulfur-coated fertilizers that utilize a partially permeable coating material for controlled N release [19][20][21]. While using enhanced-efficiency fertilizers allows for better synchronization of N supply with crop N uptake [22], high associated costs and complex production processes remain significant obstacles in their wide use [23].…”
Section: Introductionmentioning
confidence: 99%